2014
DOI: 10.1044/2013_jslhr-s-12-0345
|View full text |Cite
|
Sign up to set email alerts
|

Bilinguals Use Language-Specific Articulatory Settings

Abstract: PURPOSE Previous work has shown that monolingual French and English speakers use distinct articulatory settings, the underlying articulatory posture of a language. In the present article, the authors report on an experiment in which they investigated articulatory settings in bilingual speakers. The authors first tested the hypothesis that in order to sound native-like, bilinguals must use distinct, language-specific articulatory settings in monolingual mode. The authors then tested the hypothesis that in bilin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
40
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 25 publications
8
40
2
Order By: Relevance
“…For /ʃ/, there was a main effect of age group ( F (1,94) = 35.62, p < .001, η 2 = .268), but no main effect of gender or interaction between age and gender. Taken together, these results first confirm that the centroid frequency is very high for both fricatives in the youngest children, perhaps due to the effects on the “undifferentiated lingual gesture” of the generally high tongue tip in the “articulatory setting” of English (Wilson & Gick, 2014), and then suggest that in subsequent development, the centroid of /ʃ/ decreases with age for both genders, whereas the centroid of /s/ changes with age only for men. This interaction results in men having /s/ and /ʃ/ categories that are closer together than those of women.…”
Section: Resultssupporting
confidence: 63%
“…For /ʃ/, there was a main effect of age group ( F (1,94) = 35.62, p < .001, η 2 = .268), but no main effect of gender or interaction between age and gender. Taken together, these results first confirm that the centroid frequency is very high for both fricatives in the youngest children, perhaps due to the effects on the “undifferentiated lingual gesture” of the generally high tongue tip in the “articulatory setting” of English (Wilson & Gick, 2014), and then suggest that in subsequent development, the centroid of /ʃ/ decreases with age for both genders, whereas the centroid of /s/ changes with age only for men. This interaction results in men having /s/ and /ʃ/ categories that are closer together than those of women.…”
Section: Resultssupporting
confidence: 63%
“…For example, within a given language, speaking rate (in terms of syllables per second) may be substantially constrained by dialectal affiliation (e.g., see Jacewicz et al , 2010, for evidence of dialect-based variation in American English), and therefore an individual bilingual talker may have a relatively fast speaking rate in one language but a relatively slow speaking rate in the other language depending on the characteristic temporal patterns of the talker's dialectal affiliation in each language. Consistent with this view, Wilson and Gick (2013) demonstrated that highly proficient, balanced bilinguals adopted distinct language-specific articulatory settings for each language. This study demonstrated distinct interspeech postural settings (i.e., lip, jaw, and tongue position during inter-utterance pauses) in French and English sentence recordings by a group of French-English bilinguals, indicating that bilinguals can switch between the language-specific articulatory settings of their two languages.…”
Section: Introductionsupporting
confidence: 54%
“…Due to the highlevel analysis we employed, these results might be suggestive of a difference in articulatory settings [10] at the dialect level. However, this needs to be confirmed by focusing on the tongue position during the speakers' interspeech posture (e.g., [28]). …”
Section: Discussionmentioning
confidence: 99%